Answer:
x = - 4.5, and x = 1
Step-by-step explanation:
~ Let us solve for x through factorization, but first change the equation to an expression for the simplicity ~
1. First break this expression into groups ⇒ ( 2x^2 - 2x ) + ( 9x - 9 )
2. Now factor 2x from 2x^2 - 2x ⇒ 2x ( x - 1 )
3. Now factor 9 from 9x - 9 ⇒ 9 ( x - 1 )
3. Combine these factored expressions ⇒ 2x ( x - 1 ) + 9 ( x - 1 )
4. Factor out common term x - 1 ⇒ ( 2x + 9 )( x - 1 )
5. Now add 0 to this expression as provided in the start: ( 2x + 9 )( x - 1 ) = 0
6. And now we recieve two answers, calculated through zero product property ⇒ 2x + 9 = 0 and x - 1 = 0, ⇒ 2x = - 9 and x = 1 ⇒
x = - 4.5, and x = 1